2015
DOI: 10.1103/physreve.92.042116
|View full text |Cite
|
Sign up to set email alerts
|

Clique percolation in random graphs

Abstract: As a generation of the classical percolation, clique percolation focuses on the connection of cliques in a graph, where the connection of two k cliques means that they share at least l Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 25 publications
0
17
0
1
Order By: Relevance
“…It was found that the value of the critical exponent β depends on the definition of the order parameter [11,18]. There are two ways to define the order parameter.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…It was found that the value of the critical exponent β depends on the definition of the order parameter [11,18]. There are two ways to define the order parameter.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, for a system with the bond density p approaching the critical point p c , the corresponding mapped site percolation has the same order ofp approaching towardp c , which infers that the critical exponents of the clique percolation are identical with those of the site percolation, thus belonging to the same universality class. It is known that clique network on an ER graph can also be mapped onto a new ER graph [17,18]. However, the clique percolation on an ER graph does not belong to the same universality class as the bond percolation, as the critical exponents of clique percolation on an ER graph also depend on the value of l. These differences between the ER graph and the Moore neighborhood can be attributed to the following two factors.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Their work has been broadened to less restrictive forms of percolation. For example, two k-cliques are considered to be adjacent if they share l vertices with 1 l k − 1 [16], [17].…”
Section: Introductionmentioning
confidence: 99%